Identifikasi tumbuhan dalam masakan tradisional urap-urap sebagai materi penyusunan buku referensi taksonomi tumbuhan - Mucharommah Sartika Ami; Evi Ayu Candra (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2019)
One of the conservation efforts that needs to be implemented is plant exploration activities as local wisdom. There are various forms of local wisdom and one of them is traditional cuisine. This study aims to identify the types of plants used in traditional East Javanese cuisine, namely urap-urap. The types of plants that were identified obtained from the interview to the informant using an interview guide. Plant identification is done through direct observation using the observation sheet and the results compared with a reference scientific identification. Data were analyzed by descriptive qualitative. The results showed that there were 13 types of plants identified in traditional cuisine namely urap-urap, four types including the Monocotyledonae class and nine other types were members of the Dicotyledonae class. The 13 types of plants include Allium cepa, Allium sativum, Capsicum anuum, Capsicum frutescens, Citrus hystrix, Vigna radiata, Vigna sinensis, Ipomoea reptans, Cocos nucifera, Ocimum sanctum, Caempferia galanga, Cucumis sativus, and Caricaaya. This research concludes that 13 types of plants have been identified in traditional Javanese ointment which is Monocotyledonae and Dicotyledonae classes.